ZnO nanostructure thin film transistors on plastic substrate prepared by solution method and pH sensing properties - Feri Adriyanto; Mohd Zainizan Sahdan; Mohd Noh Dalimin; Muhammad Nizam (Universitas Sebelas Maret (UNS), 2020)
We fabricated a ZnO nanostructures based TFT on plastic substrate by solution method under low temperature. ZnO nanostructures were prepared by zinc nitrate hexahydrate, and hexamethylenetetramine. The device shows hard saturation characteristics and exhibits a high off-resistance. The output characteristics devices also shows current saturation and pinch off behavior, in which the high of current saturation obtained 266 mA at VGS = 40 V and VDS = 42.5 V. The pH response on the electrical properties was also studied. It was found that the threshold voltage shifted from 10.21 V to 13 V as pH solution gradually increased. The Ion/Ioff for as grown TFTs and TFTs with pH response of 10.21 shifted from 1.86 x 105 to 7.03 x 106 at VDS = 20 V. The obtained sensitivity of devices was 1.05 V/pH.